Experimental and numerical investigations of the influence of fluid dynamics on the precipitation of nanoscaled particles - Gradl, Johannes; Peukert, Wolfgang (4, 2007)
Continuous precipitation in a T-mixer is a promising way for the economic production of commercial amounts of nanoscaled particles. The challenge is to tailor the product properties of the precipitated particles, i.e. to control the particle size distribution (PSD). The coupling of all relevant subprocesses is the key for predicting the PSD. In this work the influence of the flow field conditions in a mixer on the precipitation process is investigated experimentally as well as numericall
Keywords: Mixing; Precipitation; Population balance equation